Distribution patterns of endemic flora to define hotspots on Hispaniola. Issue 3 (3rd May 2016) - Cano-ortiz, Ana; Musarella, Carmelo M.; Fuentes, JosÉ C. PiÑar; Gomes, Carlos J. Pinto; Cano, Eusebio
Abstract : Nineteen areas on the island of Hispaniola (Haiti and the Dominican Republic) were studied with the aim of determining the distribution pattern of the endemic flora in these areas, and their variability with altitude. The main concentration of endemic species occurs in mountains with a medium altitude and in certain mountain sites (palaeo-islands), which coincide with hotspots; a lower number of endemics are found in low-lying areas (coldspots), due to the degradation of their habitats. A total of 1, 582 endemic species were studied and were distributed in 19 areas. The whole island is of outstanding interest for its richness in endemics; it has 2, 050 endemic species, representing 34.16% of its total flora. The territory in the study is home to 1, 284 genera of which 31 are endemic to the island, including monotypical genera such as Tortuella abietifolia Urb. & Ekman, and endemic genera such as Hottea, containing seven endemic species. The sites with the highest rate of endemics are area A16 in the central range with a total of 440 endemic species, of which 278 are exclusive to the territory; and the Sierra de Bahoruco, la Selle, La Hotte and Tiburón in area A12, where we found 699 plants of which 482 are endemic and exclusive to the area; and A13 with 173 and 129 respectively. This work highlights the exceptional floristic diversity in endemic species and genera and analyses their distribution patterns as a tool for conservation in this area of the world, whose high endemicity rate makes it one of the most significant hotspots in the Caribbean.